Cost and Satisfaction Implications of Using Telehealth for Plagiocephaly. Issue 6 (20th June 2022) - Cappitelli, Alex; Wenzinger, Eric; Langa, Olivia C.; Nuzzi, Laura; Ganor, Oren; Rogers-Vizena, Carolyn R.; Ganske, Ingrid M.
Abstract : Purpose: Patients with deformational plagiocephaly are often referred for evaluation by a plastic surgeon. During the early COVID-19 pandemic, visits were performed predominantly via telehealth. This study compares costs, satisfaction, and technological considerations for telehealth and in-person consultations for plagiocephaly. Methods: This prospective study evaluated telehealth and in-person consultation for plagiocephaly between August 2020 and January 2021. Costs were estimated using time-driven activity-based costing (TDABC) and included personnel and facility costs. Patient-borne expenses for travel were assessed. Post-visit questionnaires administered to patients' families and providers measured satisfaction with the consult and technical issues encountered. Results: Costing analysis was performed on 20 telehealth and 11 in-person consults. Median total personnel and facility costs of providing in-person or telehealth consults were comparable ( P > 0.05). Telehealth visits saved on the cost of clinic space but required significantly more of the provider's time ( P < 0.05). In-person visits had an additional patient-borne travel cost of $28.64. Technical difficulties were reported among 25% (n = 5) of telehealth consults. Paired provider and patient experience questionnaires were collected from 17 consults (11 telehealth, six in-person). Overall satisfaction with care did not differ significantly between consult types or between the provider and patient family ( P > 0.05). Conclusions: Costs of providing in-person and telehealth plagiocephaly consultations were comparable, whereas patients incur greater costs when coming in person. Practices that treat patients with plagiocephaly may wish to consider expanding their virtual consult offerings to families desiring this option. Long-term outcome studies are necessary to evaluate the efficacy of both visit types.